Three-dimensional fcc C60 polymer - J. Laranjeira; L. Marques; M. Melle-Franco; K. Strutyński; M. Mezouar; M. Barroso (Materials Letters: X, 2019)
A face-centered cubic (fcc) polymerized C60 phase has been synthesized at 9.5 GPa and 550 °C. The observed short lattice constant, 13.19 Å, indicates that a three-dimensional (3D) polymer with adjacent C60 molecules covalently bonded was obtained. Possible polymerized structures, with each molecule adopting one of the two standard orientations, have been investigated through density functional theory (DFT). It was found that intermolecular bonds, 56/56 2 + 2 cycloaddition, are formed between molecules with different orientations but no bonds are formed between molecules with the same orientation. The computed bulk moduli for these structures gave values ranging from 88 to 132 GPa. Although the distances between neighboring molecules and the volume per molecule from the models are close to the experimental values, the relaxed structures displayed symmetries lower than cubic, suggesting that the experimental fcc structure is likely disordered or frustrated. Keywords: Fullerene polymers, X-ray diffraction, DFT calculations, Ordered binary-alloy structures